2021
DOI: 10.2147/jpr.s303142
|View full text |Cite
|
Sign up to set email alerts
|

Electrodiagnostic, Sonographic, and Clinical Features of Carpal Tunnel Syndrome with Bifid Median Nerve

Abstract: Purpose: A bifid median nerve (BMN) is not a rare variant. This study aimed to investigate the features of carpal tunnel syndrome (CTS) accompanied by BMN. Patients and Methods: In this retrospective study, we defined a BMN group as CTS with BMN and a non-bifid median nerve (NMN) group as CTS without BMN. All hands were assigned to four severity grades according to the findings of electrodiagnosis (EDx): very mild, mild, moderate, and severe. The cross-sectional area (CSA) of the median nerve, palmar bowing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…The moderate (S3) group included cases with abnormal transcarpal latency or sensitivity test findings, with abnormalities of the compound motor nerve action potential, and without abnormal findings of needle electromyography of the APB muscle. The severe (S4) group included those with abnormal transcarpal latency or sensitivity test findings and abnormal findings of needle electromyography of the APB muscle 24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderate (S3) group included cases with abnormal transcarpal latency or sensitivity test findings, with abnormalities of the compound motor nerve action potential, and without abnormal findings of needle electromyography of the APB muscle. The severe (S4) group included those with abnormal transcarpal latency or sensitivity test findings and abnormal findings of needle electromyography of the APB muscle 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients were asked to assume an upright sitting position and instructed to bend their elbows at 90° and fully supinate their forearms. The pisiform and scaphoid were identified at the level just proximal to the carpal tunnel, and transverse images were acquired to measure the cross-sectional area (CSA) of the median nerve 24 , 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies show that the prevalence of BMN in CTS is about 18%–18.5%, while the prevalence in normal control is approximately 9.4%–15.4%, they believed that BMN was not a rare variant and did not support its etiological relationship with CTS ( 10 , 25 ). However, Park et al ( 26 ) demonstrated that CTS with BMN showed more severe symptoms and relatively mild electrophysiological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the moderate-to-severe group included patients with abnormal findings in the motor nerve conduction studies. The detailed methods for the electrodiagnosis of CTS have been described previously [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%